Strategy for adoption of zero-tillage potato cultivation technology in Assam. RTB Policy Paper - Kumar, B.; Goswami, B.S.; Minhas, J.S. (International Potato Center, 2023)
Assam has rich soil and good natural resources for implementing climate-resilient agricultural practices to enhance potato production. Potato cultivation in the district occupies 1,03,812 hectares of land which, in 2015-2016, produced about 6,94,002 metric tons of potatoes as recorded by the Directorate of Economics and Statistics, Government of Assam1. This is quite low compared to the national average of 22 metric tons per hectare (NHB 2018). There are several reasons for the lower production of potato in Assam including low potato seed availability and low seed quality, as well as a lack of scientific knowledge on potato cultivation and pest and disease management. The Assam Agri-business and Rural Transform (APART) is a program established to develop a potato value chain in Assam to benefit farmers including addressing constraints and through farmer support to overcome them. It is carried out with support from the International Potato Center (CIP) which provides consultancy services to the Government of Assam. CIP is committed to providing cost-effective, sustainable, climate-resilient, and appropriate technological solutions to meet the unique challenges facing enhancing potato cultivation and productivity in Assam. This paper focuses on how CIP technologies can be widely disseminated to farmers in Assam in relation to current potato cultivation practices. It provides a road map for the state government to engage a large number of farmers in zero-tillage potato cultivation technology by looking at farmers’ current practices.